Influence of Torulaspora delbrueckii on the Synthesis of Flavor Compounds during the Fermentation Process of Apple Cider - Ziyi XIAO; Yuchuan ZHAO; Ling LUO; Dan HUANG; Huibo LUO; Zijian LI (Shipin gongye ke-ji)
This study utilized Torulaspora delbrueckii and Saccharomyces cerevisiae for apple cider fermentation experiments. By comparing the differences in organic acids and volatile flavor compounds between mixed fermentation and fermentation with only Saccharomyces cerevisiae, the impact of Torulaspora delbrueckii on the synthesis of flavor compounds in apple cider was investigated. The results indicated that Torulaspora delbrueckii significantly increased the levels of oxalic acid (+0.077 g/L), acetic acid (+1.68 g/L), L-lactic acid (+0.83 g/L), and succinic acid (+0.45 g/L) in apple cider (P<0.01), and reduced the quantity of higher alcohols. Co-occurrence network analysis showed that Torulaspora delbrueckii enhanced the stability of volatile flavor compound synthesis. Moreover, mixed fermentation notably increased the content of 11 volatile flavor compounds, including phenylethyl alcohol, benzaldehyde, phenethyl acetate, octanoic acid, and hexanoic acid, which would help to highlight the apple's characteristic aroma, floral and fruity scents, and enhance the perception of sweetness. Finally, based on the enrichment results of the differential flavor compound pathways, Torulaspora delbrueckii could endow the fermentation system with stronger raw material utilization capacity, sugar conversion ability, and flavor compound synthesis ability. The findings suggest that this strain has excellent mixed fermentation performance, providing a theoretical basis for its further utilization in apple cider brewing.